Genetic predisposition to elevated levels of C-reactive protein is associated with a decreased risk for preeclampsia. (2nd January 2017) - Spracklen, Cassandra N.; Smith, Caitlin J.; Saftlas, Audrey F.; Triche, Elizabeth W.; Bjonnes, Andrew; Keating, Brendan J.; Saxena, Richa; Breheny, Patrick J.; Dewan, Andrew T.; Robinson, Jennifer G.; Hoh, Josephine; Ryckman, Kelli K.
ABSTRACT: Objective : To examine the association between genetic predisposition to elevated C-reactive protein (CRP)and risk for preeclampsia using validated genetic loci for C-reactive protein. Methods : Preeclampsia cases ( n = 177) and normotensive controls ( n = 116) were selected from live birth certificates to nulliparous Iowa women during the period August 2002–May 2005. Disease status was verified by the medical chart review. Genetic predisposition to CRP was estimated by a genetic risk score on the basis of established loci for CRP levels. Logistic regression analyses were used to evaluate the relationships between the genotype score and preeclampsia. Replication analyses were performed in an independent, US population of preeclampsia cases ( n = 516) and controls ( n = 1, 097) of European ancestry. Results : The genetic risk score (GRS) related to higher levels of CRP demonstrated a significantly decreased risk of preeclampsia (OR 0.89, 95% CI 0.82–0.96). When the GRS was analyzed by quartile, an inverse linear trend was observed ( p = 0.0006). The results were similar after adjustments for the body mass index (BMI), smoking, and leisure-time physical activity. In the independent replication population, the association with the CRP GRS was also marginally significant (OR 0.97, 95% CI 0.92, 1.02). Meta-analysis of the two studies was statistically significant (OR 0.95, 95% CI 0.90, 0.99). Conclusion : Our data suggest an inverse, counterintuitive association between the genetic predisposition to elevated levels of CRP and a decreased risk of preeclampsia. This suggests that the blood CRP level is a marker of preeclampsia, but it does not appear to be a factor on the causal pathway.